First record of Dysschema sacrifica (Hübner, [1831]) on Soybean (Glycine max (L.) Merr) (Lepidoptera: Erebidae, Arctiinae) - E. González; H. M. Beccacece (SHILAP)
The presence of Dysschema sacrifica (Hübner, [1831]) on soybean (Glycine max (L.) Merr) is reported for the first time. Larvae of this species were found consuming soybean leaves in soybean fields in Córdoba province, Argentina, and were able to complete their life cycle. Characteristics of adults and larvae are provided for rapid identification in the field. Due to the widespread distribution of this species within the region where soybean is more intensively cultivated in South America, we conclude that D. sacrifica is a potential soybean pest. Further studies on infestation frequency, damage levels and control by natural enemies are needed.